Making sense by making setient effectance motivatin increases anthropomorphism.[article]. - Waytz, Adam
People commonly anthropomorphize nonhuman agents, imbuing everything from computers to pets to gods with humanlike capacities and mental experiences. Although widely observed, the determinants of anthropomorphism are poorly understood and rarely investigated. We proposed that people anthropomorphize, in part, to satisfy effectance motivation-the basic and chronic motivation to attain mastery of one's environment. Five studies demonstrated that increasing effectance motivation by manipulating the perceived unpredictability of a nonhuman agent or by increasing the incentives for mastery increases anthropomorphism. Neuroimaging data demonstrated that the neural correlates of this process are similar to those engaged when metalizing other humans. A final study demonstrated that anthropomorphizing a stimulus makes it appear more predictable and understandable, suggesting that anthropomorphism satisfies effectance motivation. Anthropomorphizing nonhuman agents seems to satisfy the basic motivation to make sense of an otherwise uncertain environment.
Keywords: Anthropomorphism; Social cognition; Motivation; Mind attribution; Unpredictability